Examination of the cut-off scores determined by the Ages and Stages Questionnaire in a population-based sample of 6 month-old Norwegian infants - Alvik Astrid; Grøholt Berit (BMC, 2011)
Abstract Background Few population-based samples have previously published performance on the Ages and Stages Questionnaire (ASQ), a recommended screening tool to detect infant developmental delay. The aim of the study was to investigate performance on the ASQ in a population-based sample of 6-month-old infants. Methods In this population-based questionnaire study from Oslo, Norway, the 30 item ASQ 6 month Questionnaire (N = 1053) were included, however without the pictograms, and compared to the Norwegian reference sample (N.ref) (N = 169) and to US cut-off values. Exclusion criteria were maternal non-Scandinavian ethnicity, infant age < 5.0 or > 7.0 months (corrected age), twins, and birth weight < 2.5 kg. Cut-off = 2.5 percentile (equivalent to mean minus 2 standard deviations). Pearson's Chi square and Mann-Whitney U were used to compare items and areas, respectively, with N.ref. Results The reported ASQ scores were lower on all but one of the 10 significantly different items, and in all areas except Personal social, compared to the N.ref sample. The estimated cut-off values for suspected developmental delay (Communication 25, Gross motor 15, Fine motor 18, Problem solving 25 and Personal social 20) were lower than the recommended American (US) values in all areas, and lower than the Norwegian values in two areas. Scores indicating need for further assessment were reached by 13.8% or 20.5% of the infants (missing items scored according to the US or the Norwegian manual), and by 33.8% or 30.3% of the infants using the recommended US or the Norwegian cut-off values, in this population-based sample. The Fine motor area demonstrated a large variability depending on the different cut-off and scoring possibilities. Both among the items excluding pictograms and the items that do not have pictograms, approximately every third item differed significantly compared to the N.ref sample. Conclusion The psychomotor developmental scores were lower than in the reference samples in this study of ASQ 6 month Questionnaire; to our knowledge the first study to be both representative and comparatively large. Approximately every third child with birth weight above 2.5 kg, received scores suggesting further assessment using recommended ASQ cut-off scores.